2017
DOI: 10.1160/th16-07-0515
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the platelet proteome in type I Glanzmann thrombasthenia caused by different homozygous delG frameshift mutations in ITGA2B

Abstract: Glanzmann thrombasthenia (GT) is one of the best characterised inherited platelet function disorders but global platelet proteome has not been determined in these patients. We investigated the proteome and function of platelets from two patients with type I GT, caused by different homozygous ITGA2b mutations, from family members and unrelated controls. The global proteome of highly purified washed platelets was quantified by liquid chromatography-mass spectrometry (LC-MS) and targeted MS-methods. Platelet func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…In agreement with previous findings 7 , 8 , 50 , both MC and FFC demonstrated CD41, CD61 and activated αIIbβ3 expression to be significantly reduced on GT platelets compared to control platelets under both non-stimulating and stimulating conditions. MC enabled us to survey an array of additional surface antigens and, in agreement with previous reports 51 55 , we found CD29, CD36, CD62P, and CD107a membrane expression to be similar on GT and control platelets following agonist stimulation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with previous findings 7 , 8 , 50 , both MC and FFC demonstrated CD41, CD61 and activated αIIbβ3 expression to be significantly reduced on GT platelets compared to control platelets under both non-stimulating and stimulating conditions. MC enabled us to survey an array of additional surface antigens and, in agreement with previous reports 51 55 , we found CD29, CD36, CD62P, and CD107a membrane expression to be similar on GT and control platelets following agonist stimulation.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to CD9, CD63 expression may be limited by membrane protein crowding, and in the absence of αIIbβ3 there would be less crowding. Interestingly, studies have shown that some GT patient platelets show increased surface expression of CD63, but not CD107a or CD62P following FcγRIIA crosslinking 55 . The investigators of these studies hypothesized that increased dense granule exocytosis was responsible for the increased surface expression of CD63 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Many signaling platelet pathways are affected by integrin out-side-in signaling, especially by the integrin α IIb β 3 . To address the possible role of the integrin α IIb β 3 for GPIbα-induced Syk activation we studied washed platelets from a patient with Glanzmann thrombasthenia (GT), which showed severe reduction of the major fibrinogen receptor α IIb ß 3 and which has been studied previously [51]. As expected, EB did not induce any aggregation response of platelets from a patient with GT, whereas platelets from a healthy control showed clear aggregation in response to EB, which was completely inhibited by the cAMP-elevating agent iloprost (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sometimes sample size is inherently limited, for instance in case of rare disorders with low prevalence, rendering the estimation of the variance uncertain. Nevertheless, such rare disorders may still be analyzed by proteomics [223]. For small sample sizes, the t-test may consider that a potential marker showing strong regulation but (concurrently) high intra-group variance is not significant [224] (Figure 6).…”
Section: Study Design For Biomarker Discoverymentioning
confidence: 99%